Poly(e-caprolactone)/poly(m-anthranilic acid) and poly(e-caprolactone)/poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) electrospun nanofibers: Characterization, antioxidant, and electrochemical properties - Huner, Keziban (WILEY, 2023)
Conducting polymers are widely used in many biomedical applications, but their non-degradability and non-biocompatibility limit their widespread use in applications. For this reason, many studies have been carried out on the developing degradable, biocompatible, and electrically conductive polymers. In this study, mixtures of conductive polymers (poly(m-antranilic acid) (P3ANA) and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS)) with biocompatible and biodegradable poly(epsilon-caprolactone) (PCL) were prepared. Their nanofibers were obtained by electrospinning and their antioxidant properties were investigated by 2,2 & PRIME;-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid (ABTS) and copper ion reducing antioxidant capacity (CUPRAC) assays. Electrochemical properties were also investigated by cyclic voltammetry and electrochemical impedance spectroscopy. The highest antioxidant activity was obtained from PCL/P3ANA3 electrospun nanofiber containing 10% (of PCL w/w) P3ANA with 93 and 614 mu g TE/mg values for ABTS and CUPRAC assays, respectively. This nanofiber was found to be non-toxic according to 2,5-diphenyl-2H-tetrazolium bromide (MTT) analysis. PCL/PEDOT:PSS electrospun nanofiber has the highest maximum anodic current value of 0.08 mA. The maximum anodic current value of PCL/P3ANA3 nanofiber with the highest amount of P3ANA is also higher than other PCL/P3ANA nanofibers. These nanofibers were characterized by FT-IR, UV-vis., XRD and TGA and their surface morphologies were examined by scanning electron microscopy (SEM).
Keywords: antioxidant properties; nanofibers; PEDOT; PSS; poly(m-antranilic acid); poly(epsilon-caprolactone); CONDUCTING POLYMERS; IN-VITRO; DEGRADATION; SCAFFOLDS; TISSUE; NANO; Engineering; Polymer Science